(untitled) (Orfeu, 2026)
This article presents the compositional planning of Sensations, for solo horn and horn quartet, focusing on the formalization of pre-compositional decisions and their articulation with extramusical references. A three-phase methodology (particularization, application, and complementation) is adopted, organizing objects, relationships, and constraints before the final writing, in dialogue with specialized bibliography and the performer, aiming for idiomatic consistency and the viability of extended techniques. The meanings of the sensations derive from John Koenig’s Dictionary of Obscure Sorrows and guide three movements. In Ambedo, the first movement, a proto-compositional system is employed, with an octatonic atmosphere and a tetrachordal derived series. In Anchorage (second movement), a semi-open system in Python converts a word into a series and matrix, guiding the selection by hexachordal combinatorics (or quasi-combinatorics). In Daguerreologue, the third movement, profile modeling generates harmonic "characters" that transform cyclically. This work proposes compositional planning procedures and poetic paths that can encourage the creation of new works from distinct initial conditions.